Dexmedetomidine and acute kidney injury following cardiac surgery in pediatric patients—An updated systematic review and meta-analysis - Wang, Hongbai; Zhang, Chaobin; Li, Yinan; Jia, Yuan; Yuan, Su; Wang, Jianhui; Yan, Fuxia (Frontiers in Cardiovascular Medicine, 2022)
Background Acute kidney injury (AKI) is a common postoperative complication in pediatric patients undergoing cardiac surgery and associated with poor outcomes. Dexmedetomidine has the pharmacological features of organ protection in cardiac surgery patients. The aim of this meta-analysis is to investigate the effect of dexmedetomidine infusion on the incidence of AKI after cardiac surgery in pediatric patients. Methods The databases of Pubmed, Embase, and Cochrane Library were searched until April 24, 2022 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. RevMan 5.3 was used to perform statistical analyses. Results Five relevant trials with a total of 630 patients were included. The pooled result using fixed-effects model with OR demonstrated significant difference in the incidence of AKI between patients with dexmedetomidine and placebo (OR = 0.49, 95% CI: [0.33, 0.73], I2 = 0%, p for effect = 0.0004). Subgroup analyses were performed based on congenital heart disease (CHD) types and dexmedetomidine intervention time. Pooled results did not demonstrate considerable difference in the incidence of AKI in pediatric patients receiving intraoperative (OR = 0.53, 95% CI: [0.29, 0.99], I2 = 0%, p for effect = 0.05) or postoperative dexmedetomidine infusion (OR = 0.56, 95% CI: [0.31, 1.04], p for effect = 0.07), but a significant difference in patients receiving combination of intra- and postoperative dexmedetomidine infusion (OR = 0.27, 95% CI: [0.09, 0.77], p for effect = 0.01). Besides, there was no significant difference in duration of mechanical ventilation (SMD: –0.19, 95% CI: –0.46 to 0.08, p for effect = 0.16; SMD: –0.16, 95% CI: –0.37 to 0.06, p for effect = 0.15), length of ICU (SMD: 0.02, 95% CI: –0.41 to 0.44, p for effect = 0.93) and hospital stay (SMD: 0.2, 95% CI: –0.13 to 0.54, p for effect = 0.23), and in-hospital mortality (OR = 1.26, 95% CI: 0.33–4.84, p for effect = 0.73) after surgery according to the pooled results of the secondary outcomes. Conclusion Compared to placebo, dexmedetomidine could significantly reduce the postoperative incidence of AKI in pediatric patients undergoing cardiac surgery with cardiopulmonary bypass (CPB), but the considerable difference was reflected in the pediatric patients receiving combination of intra- and postoperative dexmedetomidine infusion. Besides, there was no significant difference in duration of mechanical ventilation, length of ICU and hospital stay, or in-hospital mortality after surgery.